Chuck Rice, IPCC WGIII release event, April 16, 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
What the IPCC says -- Chuck Rice, Kansas State University, IPCC author Meeting global food needs with lower emissions: IPCC report findings on climate change mitigation in agriculture A dialog among scientists, practitioners and financiers April 16, 2014 World Bank, Theatre MC2-800, 1818 H Street NW, Washington, DC